Investigation of in-vitro antioxidant and cytotoxic potential of methanol extract of begonia roxburghii leaves - Chowdhury, Fowzia Afsana (BRAC University, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2017.